Editorial: Scientific advances in river restoration - Prady, Jane; Austin, Sam; Dodd, Jennifer; White, James; Wilkes, Martin; Naura, Marc (Wiley, 2025)
In September 2023, the River Restoration Centre (RRC) hosted the inaugural Scientific Advances in River Restoration (SARR) conference in collaboration with the University of Liverpool, UK. As we confront the twin crises of climate change and biodiversity loss, this event underscored the importance of global collaboration among river restoration scientists to help inform evidence‐led solutions. Fluvial systems are particularly vulnerable to global climatic pressures, with droughts and floods exacerbating the impacts of human‐induced river modifications. River restoration is a crucial tool in addressing these pervasive challenges, capable of benefiting both people (e.g., flood mitigation, community engagement) and nature (e.g., ecological recovery, ecosystem functionality). The SARR conference aimed to unite scientists from various disciplines and countries, foster collaborations, and highlight new advancements to enhance global progress in river restoration science. This river restoration special issue features a diverse selection of papers presented at the SARR conference, showcasing the multidisciplinary nature of contemporary river restoration.
Special Issue: River Restoration
Keywords: 4101 Climate Change Impacts and Adaptation; 41 Environmental Sciences; 13 Climate Action; Marine Biology & Hydrobiology; 3103 Ecology; 3707 Hydrology; 4104 Environmental management